Cadahia, Luciana; Carrasco-Conde, Ana (editoras) (2020). Fuera de sí mismas. Motivos para dislocarse. Herder. 399 páginas - Herrero Olivera, Laura (Las Torres de Lucca. International Journal of Political Philosophy, 2021)
Cadahia, Luciana; Carrasco-Conde, Ana (editoras) (2020). Fuera de sí mismas. Motivos para dislocarse. Herder. 399 páginas